JUDICIAL ACTIVISM IN INDONESIA - Rahayu Prasetianingsih (PETITA: JURNAL KAJIAN ILMU HUKUM DAN SYARIAH, 2020)
The existence of Constitutional Court becomes important as requisite for the rule of law principle and democracy in Indonesia. Amendment of the Constitution by Indonesia National Assembly has chosen to share judicial power held by the Supreme Court and Constitutional Court with the authority to judicial review of legislation to the Constitution. The Constitutional Court as Guardian of the Constitution has its own role in establishing constitutional culture in Indonesia. Commitment to constitutionalism is adistinctive constitutional culture which will also develop the constitution itself. Commitment to UUD 1945 as the limitation to the powers and a guarantee of constitutional rights that must be protected by the Constitutional Court with the authority to review as the implementation of Indonesia constitutionalism. Constitutional culture discuss in this paper is focused on understanding constitutional culture which will affect the implementation of the constitution by "the formal institutions of the state", especially in relation to the citizenry. The Constitutional Court in review of the legislation to the constitution has used various methods of Constitutional interpretation to uphold the law and substantive justice. From several decisions seem that the constitutional interpretation made by the Constitutional Court was expanding the existing notions of UUD 1945 or event change the constitution. The Constitutional Court leads to judicial activism and can be said that the constitutional court has become super body. On the other side, presence of the Constitutional Court expected to complement the government system of Indonesia, in accordance with the function can motivate the performance of other state institutions, in this case the legislator in order to establish better legislation. Abstrak: Mahkamah Konstitusi menjadi syarat penting bagi terwujudnya prinsip negara hukum dan demokrasi di Indonesia. Perubahan Konstitusi oleh Majelis Permusyawaratan Rakyat telah membagi kekuasaan kehakiman kepada Mahkamah Agung dan Mahkamah Konstitusi dengan kewenangan pengujian undang-undang terhadap Konstitusi. Mahkamah Konstitusi sebagai Penjaga Konstitusi memiliki peran tersendiri dalam membangun budaya konstitusi di Indonesia. Komitmen terhadap konstitusionalisme merupakan budaya konstitusi yang khas yang juga akan mendinamisasi konstitusi itu sendiri. Komitmen terhadap UUD 1945 sebagai pembatasan kekuasaan dan jaminan hak konstitusional yang harus dilindungi oleh Mahkamah Konstitusi dengan kewenangan pengujian sebagai implementasi konstitusionalisme Indonesia. Budaya konstitusi yang dibahas dalam tulisan ini fokus pada pemahaman budaya konstitusi yang akan mempengaruhi pelaksanaan konstitusi oleh "lembaga formal negara", terutama dalam kaitannya dengan warga negara. Mahkamah Konstitusi dalam menguji undang-undang terhadap konstitusi telah menggunakan berbagai metode penafsiran Konstitusi untuk menegakkan hukum dan keadilan substantif. Dari beberapa putusan tampak bahwa penafsiran konstitusi yang dilakukan oleh Mahkamah Konstitusi merupakan perluasan dari pengertian UUD 1945 yang sudah ada atau bahkan mengubah konstitusi. Mahkamah Konstitusi mengarah pada judicial activism dan dapat dikatakan bahwa Mahkamah Konstitusi telah menjadi super body. Di sisi lain, kehadiran Mahkamah Konstitusi diharapkan dapat melengkapi sistem pemerintahan Indonesia, sesuai dengan fungsinya dapat memotivasi kinerja lembaga negara lainnya, dalam hal ini pembentuk undang-undang agar dapat membentuk peraturan perundang-undangan yang lebih baik.Kata Kunci: Judicial Review, Penafsiran Konstitusi, Budaya Konstitusi